Nilai-nilai Kearifan Lokal dalam Adat Mamongoti Jabu di Tarutung: Studi Deskriptif - Ristomi Ricard Simatupang; Gian Aldo Sembiring; Selly Duma Agustina Situmorang; Efrida Yanti Siregar; Anggi Putri Aulia Sianturi; Mauly Purba (FKIP, Universitas Palangka Raya, 2026)
Currently, not all Batak people held the ceremony of entering a new house (Mamongoti Jabu), especially the Batak Toba people who live in urban areas due to constraints on costs, time and the next generation. Until now, research there is conducted about Mamongoti Jabu tradition is still limited in scope and not very in-depth, so there are still opportunities for more comprehensive research from various scientific points of view to reveal meaning in order to increase understanding of the Mamongoti Jabu tradition. Research Methods used in scientific articles This is a qualitative research method, with the data collection process through direct interviews with informants. Apart from direct interviews with several sources, the author also uses textual analysis methods in several books, as well as audio-visual analysis to provide an overview of the Mamongoti Jabu custom. This traditional ceremony still exists and continues to develop today, although in some places it is rare to find Batak people who perform it. The Mamongoti Jabu tradition has two types, namely Mangompoi Jabu and Manuruk Jabu. In the Mamongoti Jabu process, it starts with ribbon cutting, worship, pasahat tudu-tudu ni sipanganon, hula-hula pasahatdekke, feast (marsipanganon), sharing jambar, marhata sigabe-gabe, pasahat piso-piso dohot pasi tuak na tonggi, and hasuhuton capable. The local wisdom values ​​contained in the Mamongoti Jabu traditional ceremony in Tarutung are: mutual cooperation, togetherness and solidarity, respect for ancestors and traditions, spirituality and religiosity, as well as values ​​and cultural education for the younger generation.